Historical ecology can inform restoration site selection: the case of black abalone (Haliotis cracherodii) along California's Channel Islands. Issue 3 (9th June 2015) - Braje, Todd J.; Rick, Torben C.; Erlandson, Jon M.; Rogers‐Bennett, Laura; Catton, Cynthia A.
Abstract: Identifying appropriate ecological conditions for population restoration is important for endangered species such as black abalone ( Haliotis cracherodii ) in California, but limited information exists regarding restoration locations. Using a combination of ancient and historical archaeological data and modern commercial fishing records, four optimal locations for restoration based on past relative abundances of black abalone were identified: north‐western, north‐eastern, and south‐central San Miguel Island and western San Nicolas Island. These locations around California's Channel Islands have supported dense black abalone populations for at least 10 000 years and may offer optimal environmental conditions to enhance the success of black abalone restoration. The strategy outlined here illustrates the promise of integrating prehistoric, historical, and modern fishery data to inform restoration of threatened and endangered abalone, oysters, and other shellfish around the world. Copyright © 2015 John Wiley & Sons, Ltd.